Innovation in Political Communication Strategy: A Qualitative Approach in Examining the Influence of Campaign Messages - Patricia Ruth (Publikasi Indonesia, 2024)
This research investigates innovations in political communication strategies through a qualitative approach, focusing on the influence of campaign messages in the context of general elections in Indonesia. Through content analysis of campaign messages, this research identifies the main themes, framing strategies, and rhetoric used to influence voter perceptions. The findings of this research have practical implications for designing more effective campaign strategies, increasing more informed voter participation, and contributing new thinking to political literature and political marketing in Indonesia.